Wave-absorbing foam prepreg as well as preparation and application thereof
By combining the resin foam with pure electromagnetic matrix foam to form a double foam structure, the challenges of existing absorbing prepregs in terms of absorption bandwidth and density are solved, achieving more efficient absorption performance and lighter density.
Patent Information
- Application Number
- CN202411647114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing absorbing prepregs have challenges in improving absorption efficiency and reducing density, including narrow absorption bandwidth, high density, and intermediate layer debonding problems.
By combining the resin foam with pure electromagnetic matrix foam (such as carbon-based foam or metal matrix foam), a double foam structure is formed, and the pure resin foam is embedded using vacuum impregnation to simplify the process and improve absorption performance.
The purpose of reducing material density and widening absorption bandwidth is achieved, the absorption performance of the material is improved, and the process flow is simplified.
Abstract
Description
Technical Field
[0001] The invention relates to a wave-absorbing foam prepreg and the preparation and application thereof. Background Art
[0002] Absorbing materials are special materials that can effectively absorb electromagnetic wave energy and have a wide range of application scenarios. In order to improve the absorption efficiency, the most commonly used method in engineering applications is material compounding, that is, compounding materials with different absorption mechanisms together and adjusting the compound ratio to achieve impedance matching and electromagnetic attenuation. Among them, absorbing prepregs have the advantages of engineering application, including thickness advantages, absorbing performance advantages, shape design, product type and performance advantages, etc., and have received widespread attention. However, there are still many bottlenecks in absorbing prepregs that need to be broken through: (1) The mass is large. After adding magnetic materials (generally with high density), the mass is further improved, which is not conducive to its actual use, especially for aviation, which requires a lighter density. (2) The absorption bandwidth is narrow. Traditional prepregs often require complex multi-layer designs and multiple experiments to achieve the widening of the absorption bandwidth. (3) The middle fabric layer is prone to debonding due to thermal stress or weak shear strength in actual applications.
[0003] At present, the research and development of prepreg materials for foam interlayers is diverse. Foam interlayers can be divided into two categories: resin matrix foam and pure electromagnetic loss matrix foam. Resin matrix foam can be further divided into: pure resin foam board (CN 106147703A, CN106147702B, CN1929731A), low electromagnetic parameters are conducive to impedance matching, but not conducive to electromagnetic attenuation; resin foam board mixed with absorbent, or hard absorbing foam (CN 117246019A, CN 113942286A, CN 101700706A), enhances electromagnetic attenuation, but the blending of absorbent and resin increases the density to a certain extent, and the molding process needs to be changed accordingly according to the filling amount of the absorbent; complex structure foam layer, including hollow fabric cavity filled with absorbing foam material (CN113524820B does not specify the type of absorbing foam, CN 116512686A resin absorbing foam), enhances the mechanical properties of the material, especially solves the debonding problem, and the introduction of special hollow structure fabric will increase the complexity of fiber preparation and increase the cost on the one hand, and on the other hand, may increase the material density.
[0004] Pure electromagnetic loss matrix foam: carbon-based foam (CN 118040340A), carbon-based foam is light, porous and has good conductivity; metal matrix foam, aluminum foam (CN 111805999B), low density, and has certain wave absorption performance. However, pure electromagnetic loss matrix foam is less used and studied than resin matrix, which may be related to its poor compatibility with resin. Summary of the invention
[0005] The present invention is made in order to simultaneously achieve the purpose of reducing material density and broadening absorption bandwidth.
[0006] In the present invention, resin foam and pure electromagnetic matrix foam (carbon-based foam or metal-based foam) are combined to form a double foam structure, which can effectively simplify the process and improve the absorption performance of the material. A pure electromagnetic loss matrix foam is selected, and the pure resin foam is buried by vacuum impregnation. This is similar to the complex structure foam layer, but there are great improvements in both process and performance. The electromagnetic attenuation is mainly carried out by the pure electromagnetic loss matrix foam, and there is no need to consider the process changes brought about by the resin mixed with electromagnetic absorption powder. The pure electromagnetic loss matrix foam has a connected pore structure, which will further enhance its electromagnetic attenuation ability. The upper and lower coated films are made of materials different from the foam electromagnetic loss mechanism, which can achieve magnetic dielectric loss and optimize the wave absorption performance.
[0007] As one aspect of the present invention, it relates to an absorbing foam prepreg, comprising a pure resin film layer, a double-foam structure absorbing foam layer and an absorbing film layer arranged in sequence; wherein the double-foam structure of the double-foam structure absorbing foam layer is resin foam and pure electromagnetic matrix foam; the absorbing film layer comprises a resin mixed with a curing agent and an absorbing agent, and the absorbing agent is a magnetic absorbing agent or a dielectric absorbing agent; the resin in the resin film layer and the absorbing film layer is the same.
[0008] In a specific embodiment, the resin is bisphenol A epoxy resin or liquefied bismaleimide resin.
[0009] In a specific embodiment, the magnetic absorber is ferrite, carbonyl iron powder or magnetic metal whisker; the dielectric absorber is silicon carbide fiber, graphite, carbon black, chopped carbon fiber, graphene, carbon nanotube or conductive polymer.
[0010] In a specific embodiment, the mass ratio of the magnetic absorber in the absorbing film to the resin mixed with the curing agent is 50-70:50-30, and the mass ratio of the dielectric absorber to the resin mixed with the curing agent is 0.5-20:99.5-80.
[0011] In a specific embodiment, the thickness of the pure resin film and the wave-absorbing film are both 0.1 mm-0.25 mm.
[0012] In a specific embodiment, the pure resin film and the radar absorbing film have the same thickness.
[0013] As another aspect of the present invention, it relates to a method for preparing the above-mentioned absorbing foam prepreg, the method comprising:
[0014] 1) Preparation of microwave-absorbing adhesive film: pure resin is added with a curing agent for coating operation to obtain a pure resin adhesive film; magnetic microwave-absorbing agent or dielectric microwave-absorbing agent is dispersed in the resin mixed with the curing agent, and a coating operation is performed to obtain a microwave-absorbing adhesive film.
[0015] 2) Preparation of double foam structure absorbing foam: pure electromagnetic matrix foam is laid on the mold surface, and pure resin foaming material is filled, and the foaming material is compounded with pure electromagnetic loss matrix foam by vacuum impregnation, and the compounded foam material is placed in an oven for foaming to form a multi-layer hollow composite material. A dielectric loss type or magnetic loss type double foam structure absorbing foam is prepared.
[0016] 3) Preparation of absorbing foam prepreg: laying pure resin film, double foam structure absorbing foam and absorbing film in sequence, and preparing and forming by bag pressing, molding or autoclave method.
[0017] In a specific embodiment, in step 1), the magnetic absorber is ferrite, carbonyl iron powder or magnetic metal whisker, the dielectric absorber is silicon carbide fiber, graphite, carbon black, chopped carbon fiber, graphene, carbon nanotube or conductive polymer, and the resin is bisphenol A epoxy resin or liquefied bismaleimide resin.
[0018] In a specific embodiment, in step 1), the thickness of the pure resin film and the absorbing film are both 0.1 mm-0.25 mm, and the thickness of the pure resin film and the absorbing film are the same.
[0019] In a specific embodiment, in step 1), the mass ratio of the magnetic absorber to the resin mixed with the curing agent is 50-70:50-30, and the mass ratio of the dielectric absorber to the resin mixed with the curing agent is 0.5-20:99.5-80.
[0020] In a specific embodiment, in step 2), the pure electromagnetic matrix foam is one of cobalt foam, nickel foam, graphite-based foam, cork-derived carbon-based foam and polystyrene board-derived carbon-based foam, and the resin in the pure resin foaming material is bisphenol A epoxy resin or thermosetting 6216 phenolic resin.
[0021] As another aspect of the present invention, it relates to the application of the above-mentioned absorbing foam prepreg in the fields of aerospace, communication, electronic equipment, building materials and shoe rubber soles.
[0022] Compared with the prior art, the present invention has the following significant advantages:
[0023] The present invention aims to reduce the material density and broaden the absorption bandwidth. The conventional absorbing prepreg middle layer is replaced with foam. Different types of absorbing foam are used according to different performance requirements. The absorbing foam of the present invention effectively combines resin foam and pure electromagnetic matrix foam (carbon-based foam or metal-based foam), and takes advantage of the advantages of both foams. The adhesive film used in the prepreg can also be selected according to the performance, and a magnetic absorber is mixed in, including magnetic alloy powders such as carbonyl iron, iron, cobalt, nickel, ferrite powder, etc., or a conductive absorber is mixed in, including carbon black, carbon fiber (continuous or chopped), etc.
[0024] Taking the example of pure resin foam embedded in carbon-based foam and epoxy resin absorbing film with a small amount of carbonyl iron, the carbon-based foam has a three-dimensional interconnected conductive network to enhance the conductive loss, and the magnetic loss of the magnetic resin film, the continuous interface formed further introduces interface polarization, and the coordination of multiple loss mechanisms effectively enhances the material's ability to attenuate electromagnetic waves. At the same time, the conductive foam has many pores, which introduces multiple reflections and scattering, and further optimizes impedance matching. Therefore, the excellent effect of lightweight and broadband absorption can be foreseen. In addition, there is no need for complex layer structure design, and the preparation is simple.
[0025] Due to its excellent performance and wave absorbing properties, this material can be used in aerospace, communications, electronic equipment, confidential building materials and shoe rubber soles (lightweight and high strength) and other fields. DETAILED DESCRIPTION
[0026] In the embodiment:
[0027] The bisphenol A epoxy resin, model E51, was purchased from Guangzhou Dongjun Chemical Co., Ltd.
[0028] The liquid bismaleimide resin is N,N'-4,4'-diphenylmethane bismaleimide, which was purchased from Tiangong Sanhua Chemical Materials.
[0029] The thermosetting 6216 phenolic resin was purchased from Henan Borun New Materials.
[0030] The epoxy resin foaming agent is azodicarbonamide, model white foaming agent AG-175, purchased from Foshan Jieheng New Materials Co., Ltd. The phenolic resin foaming agent is analytical pure sodium bicarbonate, brand Xilong Science.
[0031] The water-based resin adhesive is water-based epoxy resin F0704, which was purchased from Shenzhen Yoshida Chemical Co., Ltd.
[0032] The benzyl alcohol is analytical grade benzyl alcohol, and the brand is Xilong Science.
[0033] The polyetheramine is polyetheramine D230, which was purchased from Shandong Yousuo Chemical Technology Co., Ltd.
[0034] The carbon black specification is 5000 mesh and is purchased from Huifeng Chemical.
[0035] The chopped carbon fiber is thermoplastic 6MM chopped carbon fiber yarn, which was purchased from Jusheng Carbon Fiber (Guangdong) Co., Ltd.
[0036] The graphite product number is qd-056, and it was purchased from Qiangdong Mineral Products Processing Plant in Lingshou County.
[0037] The carbonyl iron grade is JC-Fe-1, the specification is metal carbonyl iron powder, and the brand is Junchen Metal.
[0038] The type of ferroferric oxide is Iron Black No. 1, 400 mesh, and the brand is Anhong.
[0039] The nickel powder is spherical nickel powder, 500 mesh, purchased from Guangzhou Metal Metallurgy Co., Ltd.
[0040] The cobalt foam, item number JY003, and the nickel foam, item number JYS112, were both purchased from Kunshan Yizhongtian New Materials Co., Ltd.
[0041] The graphite polystyrene board, grade B1, and the thick polystyrene board, grade B1, were purchased from Ningbo High-tech Zone Huadongxing Insulation Materials Co., Ltd.
[0042] The cork coils were purchased from Pinghu Yijia Cork Manufacturing Co., Ltd.
[0043] The honeycomb core material was purchased from Zhongfang Special Fiber Co., Ltd.
[0044] The bow test is to cut the plate to be tested into 300mm*300mm plates and place them on a metal plate. When testing the absorbing performance, the transmitting antenna excites the absorbing foam prepreg, and the reflected signal is picked up by the receiving antenna. By comparing the reflected signals with and without absorbing materials, the reflectivity of the absorbing material, that is, the absorbing performance, can be calculated.
[0045] Unless otherwise specified, parts referred to in this application are parts by mass, and ratios referred to in this application are ratios by mass.
[0046] Example 1
[0047] 1) Preparation of microwave absorbing film:
[0048] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0049] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.1mm.
[0050] Carbon black was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 0.5:99.5, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.1 mm.
[0051] 2) Preparation of double foam structure absorbing foam:
[0052] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0053] Foamed cobalt (porosity 98%, thickness 2.3 mm, three-dimensional full-through mesh) was laid in a 320mm*320mm*40mm square mold, and the bisphenol A epoxy resin added with the curing agent and foaming agent was filled in the barrel to obtain a mold filled with foaming raw materials.
[0054] Place the mold filled with foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180℃ and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the foam cobalt layer to form a double foam structure absorbing foam (2.3mm), in which the yellow foam is epoxy resin foam and the gray foam is foam cobalt foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0055] 3) Preparation of microwave absorbing foam prepreg:
[0056] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing foam prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing foam prepreg.
[0057] The above-mentioned absorbing foam prepreg was tested by the bow method, and the effective absorption width obtained was close to 7GHz (11.5GHz-18GHz), and the absorption bandwidth was wide. In addition, during the operation of the embodiment, there were no problems such as the thickness of the pure resin film and the absorbing film could not be controlled, the pure resin film and the absorbing film could not be completely peeled off, and the bisphenol A epoxy resin mixed with a curing agent could not be completely mixed with carbon black (absorbent), and the surface of the obtained absorbing foam prepreg was smooth, complete and without pores.
[0058] Example 2
[0059] 1) Preparation of microwave absorbing film:
[0060] 40 parts of diallyl bisphenol A (curing agent) are added to 100 parts of liquefied bismaleimide resin to obtain liquefied bismaleimide resin mixed with curing agent.
[0061] The liquefied BMI resin mixed with curing agent is added to the coating roller, the roller is pressed against the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.2 mm.
[0062] The chopped carbon fibers were dispersed in the liquefied bismaleimide resin mixed with the curing agent in a ratio of 15:85, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing film. The thickness of the film was controlled to be 0.2 mm.
[0063] 2) Preparation of double foam structure absorbing foam:
[0064] 20 parts of sodium bicarbonate (foaming agent) are added to 100 parts of thermosetting 6216 phenolic resin to obtain thermosetting 6216 phenolic resin with foaming agent added.
[0065] Foamed nickel (porosity 98%, thickness 5mm, three-dimensional full-through mesh) was laid in a 320mm*320mm*40mm square mold, and the above-mentioned thermosetting 6216 phenolic resin with foaming agent added was filled in the barrel to obtain a mold filled with foaming raw materials.
[0066] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 175℃ and keep it warm for 2 hours. Part of the thermosetting 6216 phenolic resin with foaming agent added is embedded in the foamed cobalt layer to form a double foam structure absorbing foam (5mm), in which the yellow foam is the thermosetting 6216 phenolic resin foam and the gray foam is the foamed nickel foam. Cut off the excess thermosetting 6216 phenolic resin foam (pure yellow foam layer).
[0067] 3) Preparation of microwave absorbing foam prepreg:
[0068] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain a layer of uncured prepreg, and the two layers of uncured prepreg are stacked to obtain an uncured double-layer absorbing foam prepreg, which is prepared by a molding method: the uncured double-layer absorbing foam prepreg is placed in a hot press, a pressure of 0.05 MPa is applied, the temperature is raised to 180° C., kept warm for 2 hours, and then raised to 220° C., kept warm for 10 hours, to obtain a cured absorbing foam prepreg.
[0069] The above-mentioned absorbing foam prepreg was tested by the bow method, and the absorption bandwidth obtained was 7GHz (11GHz-18GHz). In addition, during the operation of the embodiment, there were no problems such as the thickness of the pure resin film and the absorbing film could not be controlled, the pure resin film and the absorbing film could not be completely peeled off, and the liquefied bismaleimide resin mixed with a curing agent could not be completely mixed with the chopped carbon fiber (absorbent). The surface of the obtained absorbing foam prepreg was smooth, complete and without pores.
[0070] Example 3
[0071] 1) Preparation of microwave absorbing film:
[0072] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0073] Bisphenol A epoxy resin mixed with curing agent is added to the glue coating roller, the glue roller is close to the fixed wheel, the glue coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.25mm.
[0074] Graphite was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 20:80, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.25 mm.
[0075] 2) Preparation of double foam structure absorbing foam:
[0076] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0077] Foamed nickel (porosity 98%, thickness 10 mm, three-dimensional full-through mesh) was laid in a 320 mm*320 mm*40 mm square mold, and the bisphenol A epoxy resin with curing agent and foaming agent added was filled in the barrel to obtain a mold filled with foaming raw materials.
[0078] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180°C and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the foam cobalt layer to form a double foam structure absorbing foam (10mm), in which the yellow foam is bisphenol A epoxy resin foam and the gray foam is nickel foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0079] 3) Preparation of microwave absorbing foam prepreg:
[0080] The pure resin adhesive film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing adhesive film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by an autoclave method: the uncured absorbing foam prepreg is wrapped with two aluminum plates, placed in an autoclave, the temperature is raised to 180°C, kept warm for 2 hours, and the vacuum degree is maintained at 0.6MPa to obtain a cured absorbing foam prepreg.
[0081] The above-mentioned absorbing foam prepreg was tested by the bow method, and the absorption bandwidth obtained was 8GHz (10GHz-18GHz). In addition, during the operation of the embodiment, there was no problem that the thickness of the pure resin film and the absorbing film could not be controlled, the pure resin film and the absorbing film could not be completely peeled off, and the bisphenol A epoxy resin mixed with a curing agent could not be completely mixed with graphite (absorbent). The surface of the obtained absorbing foam prepreg was smooth, complete and without pores.
[0082] Example 4
[0083] 1) Preparation of microwave absorbing film:
[0084] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0085] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.1mm.
[0086] Carbonyl iron was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 50:50, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.1 mm.
[0087] 2) Preparation of double foam structure absorbing foam:
[0088] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0089] Graphite-based foam (obtained by maintaining a 20 mm thick graphite polystyrene plate at 500°C for 1 hour under a nitrogen atmosphere) is laid in a 320 mm*320 mm*40 mm square mold, and the above-mentioned bisphenol A epoxy resin with curing agent and foaming agent added is filled in the barrel to obtain a mold filled with foaming raw materials.
[0090] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180°C and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the graphite-based foam layer to form a double-foam structure absorbing foam (20mm), in which the yellow foam is bisphenol A epoxy resin foam and the gray foam is graphite-based foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0091] 3) Preparation of microwave absorbing foam prepreg:
[0092] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing foam prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing foam prepreg.
[0093] The above-mentioned absorbing foam prepreg was tested by the bow method, and the absorption bandwidth obtained was 9GHz (9GHz-18GHz). In addition, during the operation of the embodiment, there were no problems such as the thickness of the pure resin film and the absorbing film being uncontrollable, the pure resin film and the absorbing film being unable to be completely peeled off, and the bisphenol A epoxy resin mixed with a curing agent being unable to be completely mixed with carbonyl iron (absorbing agent). The surface of the obtained absorbing foam prepreg was smooth, complete and free of pores.
[0094] Example 5
[0095] 1) Preparation of microwave absorbing film:
[0096] 40 parts of diallyl bisphenol A (curing agent) are added to 100 parts of liquefied bismaleimide resin to obtain liquefied bismaleimide resin mixed with curing agent.
[0097] The liquefied BMI resin mixed with curing agent is added to the coating roller, the roller is pressed against the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.2 mm.
[0098] Disperse ferroferric oxide in the liquefied bismaleimide resin mixed with curing agent in a ratio of 60:40, add it to the coating roller, put the roller close to the fixed wheel, start the coating machine, and coat the resin on the continuous release paper to obtain an absorbing film. The thickness of the film is controlled to be 0.2mm.
[0099] 2) Preparation of double foam structure absorbing foam:
[0100] 20 parts of sodium bicarbonate (foaming agent) are added to 100 parts of thermosetting 6216 phenolic resin to obtain thermosetting 6216 phenolic resin with foaming agent added.
[0101] Cork-derived carbon-based foam (obtained by maintaining a 5 mm thick cork coil at 500°C for 1 hour in a nitrogen atmosphere) is laid in a square mold of 320 mm*320 mm*40 mm, and the above-mentioned thermosetting 6216 phenolic resin with a foaming agent added is filled in the barrel to obtain a mold filled with the foaming raw materials.
[0102] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and place it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 175°C and keep it warm for 2 hours. Part of the thermosetting 6216 phenolic resin with foaming agent added is embedded in the cork-derived carbon-based foam layer to form a double-foam structure absorbing foam (5mm), in which the yellow foam is the thermosetting 6216 phenolic resin foam and the gray foam is the cork-derived carbon-based foam. Cut off the excess thermosetting 6216 phenolic resin foam (pure yellow foam layer).
[0103] 3) Preparation of microwave absorbing foam prepreg:
[0104] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain a layer of uncured prepreg, and the two layers of uncured prepreg are stacked to obtain an uncured double-layer absorbing foam prepreg, which is prepared by a molding method: the uncured double-layer absorbing foam prepreg is placed in a hot press, a pressure of 0.05 MPa is applied, the temperature is raised to 180° C., kept warm for 2 hours, and then raised to 220° C., kept warm for 10 hours, to obtain a cured absorbing foam prepreg.
[0105] The above-mentioned absorbing foam prepreg was tested by the bow method, and the absorption bandwidth obtained was 7GHz (11GHz-18GHz). In addition, during the operation of the embodiment, there were no problems such as the thickness of the pure resin film and the absorbing film could not be controlled, the pure resin film and the absorbing film could not be completely peeled off, and the liquefied bismaleimide resin mixed with a curing agent could not be completely mixed with ferroferric oxide (absorbent). The surface of the obtained absorbing foam prepreg was smooth, complete and without pores.
[0106] Example 6
[0107] 1) Preparation of microwave absorbing film:
[0108] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0109] Bisphenol A epoxy resin mixed with curing agent is added to the glue coating roller, the glue roller is close to the fixed wheel, the glue coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.25mm.
[0110] Nickel powder was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 70:30, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.25 mm.
[0111] 2) Preparation of double foam structure absorbing foam:
[0112] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0113] Polystyrene board-derived carbon-based foam (obtained by maintaining a 30mm thick polystyrene board at 500°C for 1 hour in a nitrogen atmosphere) is laid in a square mold of 320mm*320mm*40mm, and the above-mentioned bisphenol A epoxy resin with added curing agent and foaming agent is filled in the barrel to obtain a mold filled with foaming raw materials.
[0114] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and place it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180°C and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with a curing agent and a foaming agent added is embedded in the polystyrene board derived carbon-based foam layer to form a double foam structure absorbing foam (30mm), in which the yellow foam is bisphenol A epoxy resin foam and the gray foam is polystyrene board derived carbon-based foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0115] 3) Preparation of microwave absorbing foam prepreg:
[0116] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared by a molding method: the uncured double-layer absorbing foam prepreg is placed in a hot press, a pressure of 0.05 MPa is applied, the temperature is raised to 180° C., kept warm for 2 hours, and then raised to 220° C., kept warm for 10 hours, to obtain a cured absorbing foam prepreg.
[0117] The above-mentioned absorbing foam prepreg was tested by the bow method, and the absorption bandwidth obtained was 10GHz (8GHz-18GHz). In addition, during the operation of the embodiment, there was no problem that the thickness of the pure resin film and the absorbing film could not be controlled, the pure resin film and the absorbing film could not be completely peeled off, and the bisphenol A epoxy resin mixed with a curing agent could not be completely mixed with the nickel powder (absorbing agent). The surface of the obtained absorbing foam prepreg was smooth, complete and free of pores.
[0118] Comparative Example 1
[0119] 1) Preparation of microwave absorbing film:
[0120] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0121] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.2mm.
[0122] Carbon black was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 1:199, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.2 mm.
[0123] 2) Preparation of microwave absorbing honeycomb:
[0124] The honeycomb core material is made of Nomex material with a pore size of 2.6 mm and a height of 5 mm. 70 parts of carbonyl iron powder and 30 parts of deionized water are fully stirred and mixed to obtain a carbonyl iron powder-deionized water mixture. Then 100 parts of the carbonyl iron powder-deionized water mixture and 30 parts of a water-based resin binder are poured into a mixer and mixed for 30 minutes. During the stirring process, 30 parts of benzyl alcohol are added twice to obtain an impregnation slurry. 160 parts of the impregnation slurry are ultrasonically treated for 30 minutes, and 30 parts of polyetheramine are added three times during the ultrasonic mixing process to obtain a viscous impregnation slurry. The viscous impregnation slurry is poured into an impregnation tank and allowed to stand for 30 minutes to obtain a viscous impregnation slurry after standing. The honeycomb core material is immersed in the viscous impregnation slurry after standing. After the impregnation is completed, the honeycomb is placed in an oven at 80°C for 2 hours, and then placed on a wire rack at room temperature for 24 hours.
[0125] 3) Preparation of microwave-absorbing honeycomb prepreg:
[0126] The pure resin film prepared in step 1), the absorbing honeycomb prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing honeycomb prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing honeycomb prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing honeycomb prepreg.
[0127] Problems arise: the contact surface between the pure resin film and the absorbing film and the honeycomb is small, and the honeycomb aperture is large. During the curing process, part of the pure resin film and the absorbing film are unsupported, resulting in holes in the pure resin film and the absorbing film.
[0128] Comparative Example 2
[0129] 1) Preparation of microwave absorbing film:
[0130] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0131] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.1mm.
[0132] Carbonyl iron was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 70:30, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.1 mm.
[0133] 2) Preparation of microwave absorbing honeycomb:
[0134] The honeycomb core material is made of Nomex material with a pore size of 2.6 mm and a height of 5 mm. 1 part of carbon black is fully stirred and mixed with 199 parts of deionized water to obtain a carbon black-deionized water mixture. Then 200 parts of the carbon black-deionized water mixture and 199 parts of a water-based resin binder are poured into a mixer and mixed for 30 minutes. During the stirring process, 199 parts of benzyl alcohol are added twice to obtain an impregnation slurry. 598 parts of the impregnation slurry are ultrasonically treated for 30 minutes. During the ultrasonic mixing process, 199 parts of polyetheramine are added three times to obtain a viscous impregnation slurry. The viscous impregnation slurry is poured into an impregnation tank and allowed to stand for 30 minutes to obtain a viscous impregnation slurry after standing. The honeycomb core material is immersed in the viscous impregnation slurry after standing. After the impregnation is completed, the honeycomb is placed in an oven at 80°C for 2 hours, and then placed on a wire rack at room temperature for 24 hours.
[0135] 3) Preparation of microwave-absorbing honeycomb prepreg:
[0136] The pure resin adhesive film prepared in step 1), the absorbing honeycomb prepared in step 2), and the absorbing adhesive film prepared in step 1) are laid in sequence to obtain an uncured absorbing honeycomb prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing honeycomb prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing honeycomb prepreg.
[0137] Problem occurs: Similarly, the pure resin film and the absorbing film have a small contact surface with the honeycomb, and the honeycomb pore size is large. During the curing process, part of the pure resin film and the absorbing film are unsupported, resulting in holes in the pure resin film and the absorbing film.
[0138] Comparative Example 3
[0139] 1) Preparation of microwave absorbing film:
[0140] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0141] Bisphenol A epoxy resin mixed with curing agent is added to the glue coating roller, the glue roller is close to the fixed wheel, the glue coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.3mm.
[0142] Carbon black was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 25:75, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.3 mm.
[0143] 2) Preparation of double foam structure absorbing foam:
[0144] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0145] Foamed cobalt (porosity 98%, thickness 2mm, three-dimensional full-through mesh) was laid in a 320mm*320mm*40mm square mold, and the bisphenol A epoxy resin added with the curing agent and foaming agent was filled in the barrel to obtain a mold filled with foaming raw materials.
[0146] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180℃ and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the foam cobalt layer to form a double foam structure absorbing foam (2mm), in which the yellow foam is epoxy resin foam and the gray foam is foam cobalt foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0147] 3) Preparation of microwave absorbing foam prepreg:
[0148] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing foam prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing foam prepreg.
[0149] Problems: The thickness of pure resin film and absorbing film is too thick, and the thickness of the coating process is uncontrollable. The high mass fraction of carbon black will increase the viscosity of the resin and affect the preparation. The conductivity is too strong, the impedance is not matched, the absorption peak does not exceed -10dB (-8.5GHz), and the absorption bandwidth is 0. In addition, the surface of the absorbing foam prepreg is smooth, complete and free of pores.
[0150] Comparative Example 4
[0151] 1) Preparation of microwave absorbing film:
[0152] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0153] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.01mm.
[0154] Carbon black was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 1:999, and added to the coating roller. The coating roller was close to the fixed wheel, and the coating machine was started. The resin was coated on the continuous release paper to obtain an absorbing adhesive film. The thickness of the film was controlled to be 0.01 mm.
[0155] 2) Preparation of double foam structure absorbing foam:
[0156] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0157] Foamed cobalt (porosity 98%, thickness 1.5 mm, three-dimensional full-through mesh) was laid in a 320mm*320mm*40mm square mold, and the bisphenol A epoxy resin added with the curing agent and foaming agent was filled in the barrel to obtain a mold filled with foaming raw materials.
[0158] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180℃ and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the foam cobalt layer to form a double foam structure absorbing foam (1.5mm), in which the yellow foam is epoxy resin foam and the gray foam is foam cobalt foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0159] 3) Preparation of microwave absorbing foam prepreg:
[0160] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing foam prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing foam prepreg.
[0161] Problems: The thickness of pure resin film and absorbing film is too low to be peeled off from the release paper, and low-temperature treatment is required to partially composite with absorbing foam; the carbon black filling amount is too low, the thickness of absorbing foam is too thin, the material attenuation capacity is insufficient, the absorption peak does not exceed -10dB (-7dB), and the absorption bandwidth is 0. In addition, the surface of the obtained absorbing foam prepreg is smooth, complete and without pores.
[0162] Comparative Example 5
[0163] 1) Preparation of microwave absorbing film:
[0164] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0165] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.1mm.
[0166] Carbonyl iron was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 40:60, added to the coating roller, the roller was close to the fixed wheel, the coating machine was started, and the resin was coated on the continuous release paper to obtain an absorbing film, and the film thickness was controlled to be 0.1mm.
[0167] 2) Preparation of double foam structure absorbing foam:
[0168] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0169] Graphite-based foam (obtained by maintaining a 20 mm thick graphite polystyrene plate at 500°C for 1 hour under a nitrogen atmosphere) is laid in a 320 mm*320 mm*40 mm square mold, and the above-mentioned bisphenol A epoxy resin with curing agent and foaming agent added is filled in the barrel to obtain a mold filled with foaming raw materials.
[0170] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180°C and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the graphite-based foam layer to form a double-foam structure absorbing foam (20mm), in which the yellow foam is epoxy resin foam and the gray foam is graphite-based foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0171] 3) Preparation of microwave absorbing foam prepreg:
[0172] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing foam prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing foam prepreg.
[0173] Problems occurred: the mass fraction of carbonyl iron was too low, the material attenuation capacity was insufficient, the absorption peak did not exceed -10dB (-7dB), and the absorption bandwidth was 0. In addition, during the comparative operation, the thickness of the pure resin film and the absorbing film could not be controlled, the pure resin film and the absorbing film could not be completely peeled off, and the bisphenol A epoxy resin mixed with a curing agent could not be completely mixed with the carbonyl iron (absorbent). The surface of the obtained absorbing foam prepreg was smooth, complete and free of pores.
[0174] Comparative Example 6
[0175] 1) Preparation of microwave absorbing film:
[0176] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) are added to 100 parts of bisphenol A epoxy resin to obtain bisphenol A epoxy resin mixed with curing agent. Gluing operation:
[0177] Bisphenol A epoxy resin mixed with curing agent is added to the coating roller, the coating roller is close to the fixed wheel, the coating machine is started, and the resin is coated on the continuous release paper to obtain a pure resin film, and the film thickness is controlled to be 0.1mm.
[0178] Carbonyl iron was dispersed in the bisphenol A epoxy resin mixed with curing agent in a ratio of 80:20, added to the coating roller, the roller was close to the fixed wheel, the coating machine was started, and the resin was coated on the continuous release paper to obtain an absorbing film, and the film thickness was controlled to be 0.1 mm.
[0179] 2) Preparation of double foam structure absorbing foam:
[0180] 40 parts of 4,4'-diaminodiphenyl sulfone (curing agent) and 20 parts of azodicarbonamide (foaming agent) were added to 100 parts of bisphenol A epoxy resin to obtain a bisphenol A epoxy resin with a curing agent and a foaming agent added thereto.
[0181] Graphite-based foam (obtained by maintaining a 35 mm thick graphite polystyrene plate at 500°C for 1 hour under a nitrogen atmosphere) is laid in a 320 mm*320 mm*40 mm square mold, and the above-mentioned bisphenol A epoxy resin with curing agent and foaming agent added is filled in the barrel to obtain a mold filled with foaming raw materials.
[0182] Place the mold filled with the foaming raw materials in a vacuum drying oven, maintain a vacuum degree of 0.6MPa at room temperature, and leave it for 30 minutes. Fill the vacuum drying oven with air to restore the non-vacuum state, then raise the temperature in the vacuum drying oven to 180°C and keep it warm for 2 hours. Part of the bisphenol A epoxy resin with curing agent and foaming agent added is embedded in the graphite-based foam layer to form a double-foam structure absorbing foam (35mm), in which the yellow foam is epoxy resin foam and the gray foam is graphite-based foam. Cut off the excess bisphenol A epoxy resin foam (pure yellow foam layer).
[0183] 3) Preparation of microwave absorbing foam prepreg:
[0184] The pure resin film prepared in step 1), the double-foam structure absorbing foam prepared in step 2), and the absorbing film prepared in step 1) are laid in sequence to obtain an uncured absorbing foam prepreg, which is prepared and molded by a bag pressing method: the uncured absorbing foam prepreg is placed in a flexible rubber bag, and then placed in a vacuum drying oven, the vacuum degree is maintained at 0.6 MPa, and the temperature is kept at 180°C for 2 hours to obtain a cured absorbing foam prepreg.
[0185] Problems occurred: the mass fraction of carbonyl iron was too high and could not be completely mixed with the resin, the absorbing foam was too high, the dielectric loss part was too much, the effective magnetic dielectric loss was not achieved, the absorption peak did not exceed -10dB (-8dB), and the absorption bandwidth was 0. In addition, during the comparative operation, there were no problems such as uncontrollable thickness of pure resin film and absorbing film, and the pure resin film and absorbing film could not be completely peeled off. The surface of the obtained absorbing foam prepreg was smooth, complete and without pores.
[0186] The present invention evaluates the results from five different perspectives: film surface integrity, film thickness controllability, film strippability, resin processability, and electromagnetic wave absorption capability.
[0187] Based on the above embodiments and comparative examples, it can be seen that the embodiments of the six absorbing foam prepregs and the comparative examples of the four absorbing foam prepregs have obvious technical advantages over the comparative examples of the two absorbing honeycomb prepregs in maintaining the surface integrity of the adhesive film, ensuring the effective electromagnetic wave absorption of the adhesive film, so the absorbing foam prepreg of the present invention preferably uses a double foam structure absorbing foam. The absorbing adhesive film is a resin adhesive film added with a magnetic absorber or a dielectric absorber.
[0188] The magnetic absorber is ferrite, carbonyl iron powder or magnetic metal whisker, and the dielectric absorber is silicon carbide fiber, graphite, carbon black, chopped carbon fiber, graphene, carbon nanotube or conductive polymer.
[0189] Examples 1-6 and Comparative Examples 5 and 6 are superior to Comparative Examples 3 and 4 in terms of controllable film thickness and film stripping. It can be summarized that the thickness of the pure resin film and the absorbing film is 0.1 mm-0.25 mm. Preferably, when the thickness of the pure resin film and the absorbing film is the same, the thickness is controllable and the film can be stripped. The preparation process is summarized as follows: When performing the coating operation, the film thickness is controlled to be 0.1 mm-0.25 mm.
[0190] Examples 1-6 are superior to Comparative Examples 3-6 in terms of resin processability and electromagnetic wave absorption capacity. In summary, when the mass ratio of the magnetic absorber to the resin mixed with the curing agent in the absorbing film is 50-70:50-30, or the mass ratio of the dielectric absorber to the resin mixed with the curing agent is 0.5-20:99.5-80, the resin has good processability and strong electromagnetic wave absorption capacity.
[0191] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A microwave-absorbing foam prepreg, characterized in that: The invention comprises a pure resin film layer, a double-foam structure absorbing foam layer and an absorbing film layer which are arranged in sequence; wherein the double-foam structure of the double-foam structure absorbing foam layer is resin foam and pure electromagnetic matrix foam; the absorbing film layer comprises resin mixed with a curing agent and an absorbing agent, and the absorbing agent is a magnetic absorbing agent or a dielectric absorbing agent; the resin in the resin film layer and the absorbing film layer is the same.
2. The wave-absorbing foam prepreg according to claim 1, characterized in that: The resin in the resin adhesive film layer and the wave absorbing adhesive film layer is bisphenol A epoxy resin or liquefied bismaleimide resin.
3. The wave-absorbing foam prepreg according to claim 1, characterized in that: The magnetic absorber is ferrite, carbonyl iron powder or magnetic metal whisker; the dielectric absorber is silicon carbide fiber, graphite, carbon black, chopped carbon fiber, graphene, carbon nanotube or conductive polymer.
4. The wave-absorbing foam prepreg according to claim 1, characterized in that: The mass ratio of the magnetic absorber to the resin mixed with a curing agent in the absorbing adhesive film layer is 50-70:50-30, or the mass ratio of the dielectric absorber to the resin mixed with a curing agent is 0.5-20:99.5-80.
5. The microwave absorbing foam prepreg according to claim 1, characterized in that: The thickness of the pure resin film and the wave-absorbing film are both 0.1 mm-0.25 mm.
6. The microwave absorbing foam prepreg according to claim 1, characterized in that: The pure resin film and the wave-absorbing film have the same thickness.
7. A method for preparing a microwave-absorbing foam prepreg, characterized in that: The method comprises: 1) Preparation of microwave-absorbing adhesive film: pure resin is added with a curing agent for coating operation to obtain a pure resin adhesive film; magnetic microwave-absorbing agent or dielectric microwave-absorbing agent is dispersed in the resin mixed with the curing agent, and a coating operation is performed to obtain a microwave-absorbing adhesive film. 2) Preparation of double-foam structure absorbing foam: pure electromagnetic matrix foam is laid on the mold surface and filled with pure resin foaming material, and the foaming material is compounded with the pure electromagnetic loss matrix foam by vacuum impregnation. The composite foam material is placed in an oven for foaming to form a multi-layer hollow composite material to prepare a double-foam structure absorbing foam. 3) Preparation of absorbing foam prepreg: laying pure resin film, double foam structure absorbing foam and absorbing film in sequence, and preparing and molding by bag pressing, molding or autoclave method.
8. The method of claim 7, characterized in that In step 1), the magnetic absorber is ferrite, carbonyl iron powder or magnetic metal whisker, the dielectric absorber is silicon carbide fiber, graphite, carbon black, chopped carbon fiber, graphene, carbon nanotube or conductive polymer, and the resin is bisphenol A epoxy resin or liquefied bismaleimide resin.
9. The method of claim 7, characterized in that In step 1), the thickness of the pure resin film and the absorbing film are both 0.1 mm-0.25 mm, and the thickness of the pure resin film and the absorbing film are the same.
10. The method of claim 7, characterized in that In step 1), the mass ratio of the magnetic absorber to the resin mixed with the curing agent is 50-70:50-30, and the mass ratio of the dielectric absorber to the resin mixed with the curing agent is 0.5-20:99.5-80.
11. The method of claim 7, wherein: In step 2), the pure electromagnetic matrix foam is one of cobalt foam, nickel foam, graphite-based foam, cork-derived carbon-based foam and polystyrene board-derived carbon-based foam, and the resin in the pure resin foaming material is bisphenol A epoxy resin or thermosetting 6216 phenolic resin.
12. Application of the microwave-absorbing foam prepreg according to any one of claims 1 to 6 in the fields of aerospace, communication, electronic equipment and building materials.
Citation Information
Patent Citations
Lightweight and broadband wave absorbing material with foam sandwich structure and method for producing same
CN101700706A
A microwave absorbing composite material and its preparation method
CN106147702B
Wave-absorbing composite material and preparation method thereof
CN106147703A
A composite absorbing structure and its preparation method
CN111805999B
A microwave absorbing composite material and its preparation method
CN113524820B